Reatividade bronco-alveolar e pressoricade autocoides no pulmão perfundido do coelho - Mendonça, Maria Edilma Fernandes de (1992)
Abstract Isolated rabbit lungs were perfused with Krebs-Henseleit soution and with varying con- centrations of Dextran 70, in an open circulation perfusion system. Pulmonary functional parameters, such as pulmonary perfusion^ pressure, bronchial resis- tence and perfusate flux, were studied. These parameters were also measured 'in vitre’ during the anaphylatic reaction, in lungs isolated from rabbits previonsly sensitized with ovalbumin. The following substances were infused, separetely, during the perfusion: adrenaline, hista- mine, acetylcholine, endothelin 1 and ovalbumin. The first interesting observation was demonstrated during the infusions of adrenaline and histamine, both of which partially reversed their vasoconstrictor effect despite the continuation of infusion, which was considered the 'pulmonary vascular escape’. The development of pulmonary edema was also observed during the infusion of the above mentioned drugs, and the effect was partially reduced when the perfusion solution was substi- tuled by another containing Dextran 70. This reduction was confirmed by histopathological evaluation. Pulmonary perfusion with the infusion of adrenaline was conducted at two temperatures, 37.5aC and 25eC, and it was observed tha the funcional parameters studied were attenuated during pulmonary perfusion at 25eC, but the pulmonary vascular escape fenomenon occurred at both the temperatures. Histamine, inspite of provoking variable responses, demonstrated a tendency to raise the arterial blood pressure and bronchial resistence in controle and sensitized animais, contradicting its basic action in anaphylaxis of lowering arterial pressure. Acetylcholine did not provoke any response in bronchial resistence, as was expected ex- perimentally, and the observation remained without a specific explanation. Pilot studies with endothelin 1 were sufficient to demonstrate the lock of sensitivity of vascular and bronchial smooth muscle to this peptide. Adrenaline at the infusin doses, did not provoke bronchial resistence, at both the temperatures.